Transplantation of fecal microbiota from low to high residual feed intake chickens: Impacts on RFI, microbial community and metabolites profiles - Xie, Chunlin; Liang, Qiying; Cheng, Jiaheng; Yuan, Yushan; Xie, Lu; Ji, Jian (Poultry science, 2025)
Improving feed efficiency is vital to bolster profitability and sustainability in poultry production. Although several studies have established links between gut microbiota and feed efficiency, the direct effects remain unclear. In this study, two distinct lines of Huiyang bearded chickens, exhibiting significant differences in residual feed intake (RFI), were developed after 15 generations of selective breeding. Fecal microbiota transplantation (FMT) from low RFI (LRFI) chickens to high RFI (HRFI) chickens resulted in a reduction trend in RFI, decreasing from 5.65 to 4.49 in the HRFI recipient chickens (HFMT). Microbiota composition and functional profiles in LRFI and HFMT chickens formed a distinct cluster compared to HRFI chickens. Using 16S rDNA sequencing and RandomForest analysis, Slackia, Peptococcus, Blautia, and Dorea were identified as key microbial markers associated with feed efficiency. Additionally, untargeted metabolomics identified common differential metabolites between HFMT and LRFI vs. HRFI groups. Correlation analysis showed significant correlations between these microbial markers and differential metabolites. These findings provide a foundation for microbiome-based strategies to improve feed efficiency in poultry. [Display omitted]